Mock jurors' judgements of the victim, crime and defendant as a function of victim race and deliberation - Poli, Lynley V. (2004)
Extra-legal variables are factors within a trial that are logically irrelevant to the determination of a verdict. They are deemed extra-legal they are extra to the law and are not prescribed in the relevant statutes upon which the relevant issue must be decided. Research investigating judicial decision-making, however, demonstrates that extra-legal variables often affect jurors' judgements and improperly influence their decision-making. Examples of extra-legal variables include the personal attributes of trial participants, e.g., the victim's physical attractiveness, socio-economic status, and age. Studies conducted in North America indicate that the race of the victim and defendant inappropriately influences jurors' decision-making. However, to date, no such published research has been conducted in Australia. Due to Australia's diverse population, which consists of several minority groups and a dominant Caucasian group, it is likely that race may net as an extra-legal variable. Furthermore, several Australian studies have documented a strong prejudice against Aborigines and Asians, with the potential for a newly emerging prejudice against individuals from Middle-Eastern countries. The present study investigated whether the race of the victim would affect jurors' perceptions and judgements in a simulated attempted-rape trial. Research also indicates that the process of deliberation amongst other things, can affect the influence of extra-legal variables on decision-making, and that it can either exaggerate or attenuate this influence. Therefore, the impact of deliberation on the jurors' perceptions and judgements was investigated, and also whether an interaction occurred between race and deliberation. One hundred and six participants were recruited to examine the effects of the race of the victim on their judgements of the defendant, crime, and victim. Due to Australia having a dominant Caucasian race, it was assumed that when the victim is Aboriginal, Asian or of a Middle Eastern origin, jurors' judgements of the defendant, crime and the victim will be negatively prejudiced by the victim's race, and that when the victim is Caucasian, no such prejudice will impact upon the jurors' decision-making. It was also assumed that deliberation would attenuate the influence of the extra-legal variable of the victim's race, such that any bias observed in pre-deliberation judgements will be reduced in post deliberation judgements. The quantitative data was analysed with a series of 4 x 2repeated measures ANOVAs and a qualitative analysis was undertaken of the deliberation discussions. Quantitative results revealed no significant effects for victim race. However, the effect for race approached significance regarding the seriousness of the crime, with the crime perceived as least serious for the Middle-Eastern victim. The pattern of results identified across several items also revealed a consistent trend toward the different races. An overall positive trend was observed toward the Aboriginal victim, and a negative trend identified toward the Middle-Eastern victim, and to a lesser extent, the Caucasian victim. Qualitative analyses support this pattern of results. The effect for deliberation revealed a number of significant findings, with the victim's character perceived as more positive, and the defendant as less guilty following deliberation. Significant interactions were also identified regarding the defendant's sentence and the responsibility of the victim. In particular, following deliberation, the defendant in the Caucasian condition was given a significantly reduced sentence, and the Asian victim was perceived as significantly less responsible. The results are discussed in terms of the need for closer analyses of Australian intergroup relations, social desirability and cultural stereotyping, and their influence on courtroom decisions